2003
DOI: 10.1523/jneurosci.23-23-08281.2003
|View full text |Cite
|
Sign up to set email alerts
|

Slow Oscillation in Non-Lemniscal Auditory Thalamus

Abstract: In the present study, we investigated the oscillatory behavior of the auditory thalamic neurons through in vivo intracellular and extracellular recordings in anesthetized guinea pigs. Repeated acoustic stimulus and cortical electrical stimulation were applied to examine their modulatory effects on the thalamic oscillation

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
33
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 101 publications
9
33
0
Order By: Relevance
“…1 A) indicated that 2 of 4 cells recorded in the ventral division (lemniscal nucleus) and 4 of 5 cells in the dorsal and caudomedial divisions (nonlemniscal nucleus) of the MGB showed up and down states, suggesting that slow oscillations are more prominent in the nonlemniscal nucleus. Similar to that reported previously (He, 2003), we found that the auditory response latency of the nonlemniscal neurons (29.0 Ϯ 15.7 ms, SD, n ϭ 5) was longer than that of the lemniscal cells (15.2 Ϯ 3.8 ms, n ϭ 4) in the population of neurobiotin-labeled neurons. We thus used response latency as a criterion to select two groups of cells from the recorded pool: lemniscal cell-like (with latency Ͻ10 ms) and nonlemniscal cell-like (with latency Ͼ20 ms).…”
Section: Bistable Membrane Potentials Of Auditory Thalamic Neurons Insupporting
confidence: 90%
See 3 more Smart Citations
“…1 A) indicated that 2 of 4 cells recorded in the ventral division (lemniscal nucleus) and 4 of 5 cells in the dorsal and caudomedial divisions (nonlemniscal nucleus) of the MGB showed up and down states, suggesting that slow oscillations are more prominent in the nonlemniscal nucleus. Similar to that reported previously (He, 2003), we found that the auditory response latency of the nonlemniscal neurons (29.0 Ϯ 15.7 ms, SD, n ϭ 5) was longer than that of the lemniscal cells (15.2 Ϯ 3.8 ms, n ϭ 4) in the population of neurobiotin-labeled neurons. We thus used response latency as a criterion to select two groups of cells from the recorded pool: lemniscal cell-like (with latency Ͻ10 ms) and nonlemniscal cell-like (with latency Ͼ20 ms).…”
Section: Bistable Membrane Potentials Of Auditory Thalamic Neurons Insupporting
confidence: 90%
“…The average interval between the onset times of two adjacent down states (equivalent to the sum of the mean durations of up and down states) was 10.1 Ϯ 5.7 s (SD, n ϭ 121; range, 2 to 30 s) (Fig. 1 E), consistent with the frequency of previously observed slow oscillations in auditory thalamic neurons (He, 2003). For each given cell, the interval was highly variable (Fig.…”
Section: Bistable Membrane Potentials Of Auditory Thalamic Neurons Insupporting
confidence: 86%
See 2 more Smart Citations
“…First, burst firing acts as an effective relay and amplifying signal in vivo [68][69][70][71]. Burst firing performs better signal detection [70,72], effectively relays auditory information in a non-linear input-output manner, regulates the frequency selectivity of MGB neurons [70,73,74], and may be involved in the generation of oscillations [75,76]. Second, RD and rebound spikes may be directly responsible for neuronal off-responses [8,77,78], which are shown by MGB neurons [79,80].…”
Section: Kir Channels Regulate Rd By Changing the Resting Membrane Pomentioning
confidence: 99%